The Effect of Compensation and Competence on Employee Performance Through Organizational Commitment as an Intervening Variable: JEL Classification: M12, M53, M54, J24, D23 - Budi, Alfian; Wibowo, Wibowo; Kurnia, Luki (Newinera Publisher, 2025)
This study aims to examine the direct influence of compensation, employee performance, and organizational commitment, as well as the indirect influence of compensation and competence, mediated by organizational commitment, at the Gerindra Party Branch Office in Demak Regency. This is due to several factors, including the substandard quality of human resources, as evidenced by the presence of the smart system, which has led to poor employee performance. Employee competencies in skills, knowledge, and attitude are still relatively low, given that most employees have a high school education background compared to diploma and bachelor's degrees. Compensation related to bonuses received by these employees is very low, impacting their performance. Difficulty using the smart system application has resulted in a decline in legislative candidate performance in increasing both candidate and party votes. Employee organizational commitment is suboptimal. The research method used is an associative quantitative method with a correlational approach. The population in this study was all 70 employees of the Demak Branch Office. The sampling technique was saturated sampling. The data collection process used a questionnaire administered to 70 respondents. This study employed linear regression analysis using SPSS software. The results of the study indicate that compensation significantly influences employee performance. Competence significantly influences employee performance, organizational commitment significantly influences employee performance, compensation significantly influences organizational commitment, competence significantly influences organizational commitment, organizational commitment can mediate the effect of compensation on competence, and organizational commitment can mediate the effect of competence on employee performance